Implementasi Game-Based Learning Berbasis Memory Game dalam Meningkatkan Daya Ingat Peserta Didik pada Pelajaran Pendidikan Agama Islam - Naufal Fadhli Ramadhan; Gilang Maulana Jamaludin; Herdianto Wahyu Pratomo (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The low memory retention of students toward Islamic Religious Education (IRE) material is a problem that needs to be addressed through innovative learning media. This study aims to improve the retention of fourth-grade students at SDN Liangjulang VI through the implementation of game-based learning using a memory game. The study employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted in two cycles, with 19 students as research subjects. Data collection instruments included pre- and post-tests consisting of 15 multiple-choice questions, observations, and documentation. Data were analyzed using descriptive quantitative methods based on memory retention percentages and classical mastery rates. The results showed a consistent improvement in memory retention from 51.22% in the pre-cycle (classified as “Low”), increasing to 57.89% in Cycle I, and reaching 77.18% in Cycle II (classified as “High”). Classical mastery increased from 26.3% to 89.5%, exceeding the success criterion of ≥85%. The memorize-recall-examine mechanism in the memory game was proven to stimulate the transfer of information from short-term memory to long-term memory through structured active repetition.